(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2023)
This article focuses on ways to develop and strengthen national spiritual immunity in the hearts of the younger generation today and to improve their innovative activity. It outlines ways to educate well-off young people and address a number of problems that hinder the development of our society.